The monument as a testimony: historical and constructive research of the hermitage of Saint Margaret of Abejuela (Teruel, Spain) and proposals of intervention - Sánchez Zuriaga, Domingo (2018)
Far from the village of Abejuela, which currently belongs to, and located in the highlands of the Javalambre sierra, the hermitage of Saint Margaret is a small sized and poor-appearance building. The interior, however, shows us a great example of medieval church with diaphragm arches and wooden frame. Research carried out on the building during the years 2006 and 2007 will allow us to identify its origin, locate and date different construction stages, and even venture their promoters. The methodology applied, ranging from surveying to archival research, including constructive and chemical analysis, will allow us to advance in knowledge not only of the building but also of the population it served as a parish, and also of the entire area, former border between realms. All these findings should be applicable to future interventions in the building and its surrounding area.